2020
DOI: 10.1016/j.ijpam.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The first report of Methicillin-resistant Staphylococcus aureus (MRSA) in cystic fibrosis (CF) patients in Saudi Arabia

Abstract: Introduction Methicillin-resistant Staphylococcus aureus infections have been increasingly reported in patients with cystic fibrosis (CF) who have progressive deterioration in their pulmonary function. Objectives To determine the prevalence of MRSA infections in CF in a tertiary care center in Saudi Arabia. Methodology This is a retrospective chart review conducted as part of the CF registry data from 1 January 2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…identical to our study [35,36]. Several reports have suggested that chronic MRSA infection is associated with a high decline rate of lung function, failure to recover lung function after a pulmonary exacerbation and decreased survival [37,38]. Te prevalence of MRSA in our study was 20% which is similar to Chmiel et al who reported the prevalence of MRSA infection at 25% in the USA, as compared to 11% in Canada and Europe [39].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…identical to our study [35,36]. Several reports have suggested that chronic MRSA infection is associated with a high decline rate of lung function, failure to recover lung function after a pulmonary exacerbation and decreased survival [37,38]. Te prevalence of MRSA in our study was 20% which is similar to Chmiel et al who reported the prevalence of MRSA infection at 25% in the USA, as compared to 11% in Canada and Europe [39].…”
Section: Discussionsupporting
confidence: 90%
“…In 2008, 50.9% of CF patients included in the cystic fibrosis foundation (CFF) patient registry had positive S. aureus cultures and the most affected groups were children between 6 to 10 and adolescents of 11 to 17 years of age which is identical to our study [ 35 , 36 ]. Several reports have suggested that chronic MRSA infection is associated with a high decline rate of lung function, failure to recover lung function after a pulmonary exacerbation and decreased survival [ 37 , 38 ]. The prevalence of MRSA in our study was 20% which is similar to Chmiel et al who reported the prevalence of MRSA infection at 25% in the USA, as compared to 11% in Canada and Europe [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, prevalence of MRSA infections in patients with cystic fibrosis (CF) has risen from 12% in 2003 to nearly 26% in 2013, with serious lung function impairment and subsequent mortality 44 . In a recent retrospective chart review, MRSA incidence among CF patients in Saudi Arabia was reported to be 11% 45 . Due to serious MRSA complications in CF patients, its eradication must be considered and it was found that a combination of oral rifampicin and nebulized vancomycin remained one of the successful eradication regimens 46 .…”
Section: Results and Discussion Prevalence Of Mrsa In Saudi Arabiamentioning
confidence: 99%